A meta-analysis of the effects of strength training on physical fitness in dancers - Yang, Yunqing; Deng, Nuannuan; Yang, Xinggang (Frontiers in Physiology, 2025)
BackgroundPhysical fitness is fundamental for successfully carrying out daily tasks and activities associated with dance. This meta-analysis aimed to evaluate the impact of strength training on various aspects of physical fitness in dancers.MethodsA comprehensive search of Web of Science Core Collection, PubMed, SPORTDiscus, SCOPUS, Cochrane library, CINAHL, and Embase was conducted until 10 December 2024, supplemented by hand-searches via Google Scholar and reference lists of included studies. Controlled trials that assessed the effects of strength training on at least one physical fitness measure in dancers were selected. Effect sizes (ES, Hedges’ g) were calculated using a random-effects model to compare experimental and control groups. Study quality was assessed using the Cochrane risk of bias tools.ResultsA total of 15 studies, involving 351 dancers, met the eligibility criteria. The analyses revealed significant moderate to large effects of strength training on muscle strength (ES = 1.84; 95% CI: 0.90 to 2.77; p < 0.001) and muscle power (ES = 0.64; 95% CI: 0.30 to 0.98; p < 0.001). Non-significant effects (all p > 0.05) were found for body mass (ES = 0.13; 95% CI: −0.32 to 0.58; p = 0.572), body fat percentage (ES = 0.08; 95% CI: −0.04 to 0.61; p = 0.754), cardiorespiratory endurance (ES = 0.28; 95% CI: −0.48 to 1.04; p = 0.469), and flexibility (ES = 0.37; 95% CI: −0.06 to 0.79; p = 0.090).ConclusionThe findings indicate that strength modalities, including resistance training, plyometric training, weight training, and combined programs, positively impact muscle strength and power in dancers. However, future research should explore the effective training parameters (e.g., frequency, session length, intensity, and specificity of strength exercises) necessary to improve not only strength and power but also other components of physical fitness in dancers.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=596550, Identifier CRD42024596550.